(untitled) (Development Engineering Conferences Center Articles Database, 2025)
This narrative review synthesizes and critically evaluates the existing literature on the transformative influence of audiovisual media on human EEG brainwave patterns. The primary objective is to construct a coherent conceptual framework by integrating findings from cognitive neuroscience, psychology, and media studies. The review traces the historical paradigm shift from studying simple sensory stimuli to employing ecologically valid, naturalistic media, which has revealed the brain as an active, predictive interpreter of narratives. Key themes explored include the neural mechanisms of multisensory integration, the modulation of specific brainwave oscillations (e.g., alpha, beta, theta, gamma) by media content and genre, and the role of narrative structure and emotional arousal in driving intersubject neural synchrony. The review also appraises the distinct neural signatures elicited by emerging technologies like virtual reality and considers the mediating role of individual differences. A critical discussion highlights theoretical frameworks such as Neurocinematics and the Brain-as-Predictor model, while also addressing methodological challenges in capturing continuous brain dynamics. The findings underscore that audiovisual media does not induce a simple stimulus-response loop but engages a complex interplay of sensory processing, cognitive resource allocation, and emotional resonance. The conclusion emphasizes the significant translational potential of these insights in clinical, educational, and entertainment domains, bridging a critical gap in the interdisciplinary understanding of how real-world stimuli shape brain function.